Sensitivity and Specificity of Pulse Oximetry for Congenital Heart Disease Screening in Newborn: A Meta-Analysis - Ilma Syifannisa; Raden Ayu Libert Gatho Reza Valentine; Dodo Islamuddin Khomara Rangkuti (GHMJ (Global Health Management Journal), 2024)
Background: Early detection for Congenital Heart Disease (CHD) using pulse oximetry is a routine procedure for newborn. Pulse Oximetry Screening (POS) has been shown to be effective in detecting CHD. Aims: To evaluate the accuracy of POS through sensitivity and specificity in detecting CHD.   Methods: In this meta-analysis, we conducted a search on Pubmed, Scopus, and ScienceDirect for studies that were published up to June 20, 2024. We selected studies that assessed the sensitivity and specificity of POS for the screening of CHD in newborn babies in a hospital or home setting, regardless of gestational age at birth and excluded newborns with a previous diagnosis of CHD. We used RevMan5 software (QUADAS-2: Quality Assessment of Diagnostic Accuracy Studies-2) to assess the quality of the studies included and used Stata/SE 16.0 software to pool the sensitivity and specificity. Results: The results showed that 17 studies, including 413,516 newborns, had pooled sensitivity and specificity of 0.69 (95% CI: 0.57-0.81) and 0.93 (95% CI: 0.85-1.00). Conclusion: This study’s results suggest that POS has moderate sensitivity and high specificity in screening CHD in newborns. It can be concluded that there is a prospective usefulness of POS as a valuable tool in clinical practice for screening and management of CHD, especially in settings where access to higher diagnostic technologies may be limited.   Received: 25 September 2024  |  Reviewed: 20 October 2024  |  Revised: 13 November 2024  |  Accepted: 30 November 2024.